Reinvigorating the Study of Opportunism in Supply Chain Management. Issue 1 (13th January 2020) - Lumineau, Fabrice; Oliveira, Nuno
Abstract : Opportunism is a core issue in supply chain management. However, assumption‐omitted testing and a focus on general opportunism as opposed to specific forms of opportunism have stubbornly limited our understanding of this construct. Grounded in a review of empirical studies of opportunism, we identify empirical challenges that perpetuate conceptual limitations in the study of opportunism in supply chains. Hence, we provide suggestions about research designs and data sources that support an agenda that steers research to refine and develop the theory about opportunism. Our call for a reinvigoration of the study of opportunism supports rigor—by discussing research design and data sources—and relevance—by identifying topics for future supply chain research.